EFFECT OF ALGINATE/CALCIUM CONCENTRATION ON PHYSICAL AND SENSORY PROPERTIES OF FAT EXTENDERS EFECTO DE LA CONCENTRACIÓN ALGINATO/CALCIO SOBRE LAS PROPIEDADES FÍSICAS Y SENSORIALES DE EXTENSORES GRASOS - Waldir A. PACHECO P. (Universidad de Antioquia, 2012)
The fat extenders are fat replacer that can be used to provide some or all of the functions of fat in the meat products, yielding fewer calories than fat. The influence of several sodium alginate (0.69% - 2.81%) and calcium carbonate (0.21% - 0.84%) concentrations on the texture, melting point, and sensory properties of fat extenders made from pork back fat, and a mixture of the above two variables have been studied using a central composite rotable design and response surfaces. Sodium alginate and calcium carbonate concentration revealed a significant effect (p ≤ 0.05) on the texture parameters. In melting properties, there were not significant effects (p ≤ 0.05) on the established limit for variables, except for melting peak temperature. In sensory attributes, they had significant differences (p ≤ 0.05) between fat extenders and the standard, in regard to shine, color and hardness. Therefore, fat extenders made with the addition of 1.0% sodium alginate and 0.79% calcium carbonate displayed textural and melting point properties with higher values in comparison with other treatments, along with sensory characteristics closer to the standard. Los extensores grasos son reemplazantes de grasa que se pueden utilizar para proporcionar algunas o todas las funciones de la grasa en un producto cárnico, produciendo menos calorías que la grasa. El efecto de varias concentraciones de alginato de sodio (0,69% - 2,81%) y carbonato de calcio (0,21% - 0,84%) sobre las propiedades de textura, fusión y sensoriales de extensores grasos elaborados a parir de tocino de cerdo y la mezcla de estas dos variables, se estudió mediante el empleo de un diseño compuesto central rotable y superficies de respuesta. La concentración de alginato de sodio y carbonato de calcio mostró efectos significativos (p ≤ 0,05) sobre los parámetros de textura. Para el caso de las propiedades de fusión, no hubo efectos significativos (p ≤ 0,05) de estas variables sobre los parámetros establecidos, excepto en el caso de la temperatura pico de fusión. En cuanto a los atributos sensoriales se encontró diferencias significativas (p ≤ 0,05) entre los extensores grasos y el control en cuanto al brillo, color y dureza. Extensores grasos elaborados con niveles de alginato de sodio alrededor del 1,0% y de carbonato de calcio del 0,79% mostraron propiedades de textura y fusión con valores más altos en comparación con los demás tratamientos; así como características sensoriales más cercanas al control.